Request to separate completed temporary works from the CAR sum insured - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to separate completed temporary works from the insured CAR sum of BRACU new campus project.